SPECIMEN EXAMINATION FOLLOWING SURGERY FOR RECTAL CANCER: OUR TECHNIQUE - O. N. Ponkina; V. V. Polovinkin (Инновационная медицина Кубани)
Standard surgical treatment for rectal cancer is a total mesorectumectomy (TME) and it demands performing proper pathohistological examination of the removed specimen to select patients with high risk of local recurrence development and those indicated for adjuvant therapy. Pathologists should value quality of surgical intervention, examine both distal and circular resection margins (surgically mobilized mesorectal surface), define surgical clearance (distance from the circular resection margine to the tumor itself), perform pathological staging ((у)pTpN), determine histological type and stage of tumor differentiation. In this paper we describe a route of the specimen removed after the surgery for rectal cancer and its pathohistological examination technique which is based on the guidances of the British Royal Society of Pathologists specialized to the Regional Clinic Hospital requirements.